2022
DOI: 10.1186/s40538-022-00295-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant hormone crosstalk mediated by humic acids

Abstract: Background The reliance on chemical inputs to support high yields is the Achilles’ heel of modern crop production. The soil organic matter management is as old as agriculture itself. Recently, the use of soluble humic substances as plant growth promoters has been brought to attention due to their effects on nutrient uptake and water use efficiency. Humic substances applied directly at low concentrations can trigger different molecular, biochemical, and physiological processes in plants. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 197 publications
2
20
0
Order By: Relevance
“…DNA replication licensing factor MCM2 [ 77 ] and WEB family proteins [ 78 , 79 ] are synchronized and prepare the cell cycle progression, respectively, while leucine-rich repeat-containing protein DDB is involved in chromatin and DNA dynamics [ 79 ]. On the other hand, DeSI-like (peptidase-like) protein is a protein involved in nitrogen catabolism [ 52 , 80 , 81 ], and these nitrogen derivates could be translocated and transformed into nitrogen reserves in seeds or be responsible for the emergence of seedlings [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA replication licensing factor MCM2 [ 77 ] and WEB family proteins [ 78 , 79 ] are synchronized and prepare the cell cycle progression, respectively, while leucine-rich repeat-containing protein DDB is involved in chromatin and DNA dynamics [ 79 ]. On the other hand, DeSI-like (peptidase-like) protein is a protein involved in nitrogen catabolism [ 52 , 80 , 81 ], and these nitrogen derivates could be translocated and transformed into nitrogen reserves in seeds or be responsible for the emergence of seedlings [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in P. calyculatus , that infects mesquite trees, there are no reports indicating that it secretes lignocellulolytic and peptidase enzymes. In that sense, we detected a group of proteins that were accumulated in the main infective stages such as pectinesterase 15 and DeSI-like (peptidase-like) protein that are likely cell wall-degrading and peptidase enzymes, respectively [ 52 , 53 , 54 , 80 , 81 , 116 ]. A pectin methylesterase enzyme was secreted from calli and seedlings of Orobranche aegyptiaca and O. cumana and it was speculated that the enzyme may have a function in host infection [ 51 , 117 , 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that some biostimulant effects of HS originate from their impact on structural and physiological modifications in roots and shoots related to nutrient assimilation and soil distribution ( Canellas et al., 2015 ). Also, HS can simultaneously regulate the transcription and activity of some plant hormones following addition to the rhizosphere ( Souza et al., 2022 ). Recently, it has been demonstrated that HS can alter the plant microbiome by favoring the recruitment of beneficial microorganisms after application ( da Silva et al., 2021 ).…”
Section: Biostimulant Materialsmentioning
confidence: 99%
“…HS are extracted from soils, sediments, composted biomasses, or agro-industrial residues and might be regarded as supramolecular associations of small, heterogeneous molecules held together in metastable structures by non-covalent interactions (van de Waals, p-p, H-bonds; metal bridges) [34,53]]. The molecular heterogeneity and conformational complexity of HS explains the range of different effects on plant metabolism [29,30,47]. Numerous experimental evidence showed that humified organic matter stimulates plant growth and is capable of significantly improving crops yields [1,8].…”
Section: Introductionmentioning
confidence: 99%